Hambatan Siswa dalam Mematuhi Peraturan Sekolah - Pertiwi, Desi Yuscha; Ibrahim, Yulidar; Ifdil, Ifdil (Universitas Negeri Padang, 2014)
Conducive conditions of school make support students to develop their potential. In order to create conducive environment, it is required rules and regulations to organize student’s behavior. Base of phenomena, there are plenty of students whose break the rules. This research objective is to describe barriers that students in order to abide school’s rules in study, dress, and time. This research use descriptive method with purposive random sampling technique amount of 50 students. Instrument use questioner student’s barrier in complying school’s rules and regulations with r 0.966. Results of this research reveal that student’s barriers in complying school’s rules and regulations for study, dress, and time are 63.4%, 59.3%, and 56.9% respectively. It is suggested for counselors to guide their students to complying school’s rules and regulations and develop student’s awareness in the importance of school’s rules and regulations.